2017
DOI: 10.1002/lpor.201700222
|View full text |Cite
|
Sign up to set email alerts
|

Novel BeZnO Based Self‐Powered Dual‐Color UV Photodetector Realized via a One‐Step Fabrication Method

Abstract: In this work, we fabricated a novel BeZnO based dual‐color UV photodetector through a one‐step electron beam evaporation of asymmetric Ti/Au pair. A dual‐phase BeZnO alloy film with dual bandgap of ∼3.5 eV (∼355 nm) and ∼4.6 eV(∼270 nm) was artfully utilized as active layer to realize dual‐color response. This photodetector shows a noticeable photovoltaic characteristic and can be utilized as an excellent self‐powered device. The device exhibits two cut‐off response wavelengths at ∼275 nm and ∼360 nm under zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…Thus, the relatively long trapping time and short transit time leads to a high gain. In addition, an ultrahigh and stable photocurrent of ≈4 mA at 3 V is observed (see Figure b), exceeding that of most PDs reported in literature (see details in Table S2, Supporting Information), which suggests that it can be easily integrated with a commercial data reader and a wireless data transporter that typically require a threshold current of ≈ 1 mA. The correlation between photocurrent and power density of such device was also calculated, as indicated in Figure c.…”
mentioning
confidence: 69%
“…Thus, the relatively long trapping time and short transit time leads to a high gain. In addition, an ultrahigh and stable photocurrent of ≈4 mA at 3 V is observed (see Figure b), exceeding that of most PDs reported in literature (see details in Table S2, Supporting Information), which suggests that it can be easily integrated with a commercial data reader and a wireless data transporter that typically require a threshold current of ≈ 1 mA. The correlation between photocurrent and power density of such device was also calculated, as indicated in Figure c.…”
mentioning
confidence: 69%
“…[ 1–3 ] To develop multispectral detection, researchers have initially focused on dual‐color detection, and a series of UV/UV, UV/visible, UV/infrared (IR), visible/IR, and IR/IR dual‐color photodetectors have been proposed. [ 4–8 ] However, the current dual‐color photodetectors heavily rely on epitaxial inorganic semiconductors with alloy, superlattice and multiple quantum well structures. [ 8–11 ] To obtain high‐performance dual‐color photodetectors, it is challenging to overcome lattice and thermal mismatch between the semiconductor layers in epitaxial growth.…”
Section: Figurementioning
confidence: 99%
“…Although both the broadband and narrowband photodetectors have already achieved high performance, these photodetectors can exclusively operate under single spectral response model and consequently exhibit single response spectrum, limiting their broader applications. Realizing highly sensitive multifunctional photodetectors with tunable spectral response ability would meet the need of versatility in practical application …”
Section: Research Trends On Pm Type Opdsmentioning
confidence: 99%
“…Realizing highly sensitive multifunctional photodetectors with tunable spectral response ability would meet the need of versatility in practical application. [171][172][173][174][175] The OPDs with tunable spectral response upon bi-directional illumination have been realized by utilizing thin metal or conducting polymer as semitransparent electrode. [88,[176][177][178][179][180] Wu et al demonstrated the OPDs with thin metal cathode, exhibiting tunable response wavelength.…”
Section: Multifunctional Organic Photodetectorsmentioning
confidence: 99%